Wood‐inhabiting fungi with tight associations with other species have declined as a response to forest management. Issue 2 (13th September 2016) - Abrego, Nerea; Dunson, David; Halme, Panu; Salcedo, Isabel; Ovaskainen, Otso
Abstract : Research on mutualistic and antagonistic networks, such as plant–pollinator and host–parasite networks, has shown that species interactions can influence and be influenced by the responses of species to environmental perturbations. Here we examine whether results obtained for directly observable networks generalize to more complex networks in which species interactions cannot be observed directly. As a case study, we consider data on the occurrences of 98 wood‐inhabiting fungal species in managed and natural forests. We specifically ask if and how much the positions of wood‐inhabiting fungal species within the interaction networks influence their responses to forest management. For this, we utilize a joint species distribution model that partitions variation in species occurrences among environmental (i.e. resource availability) and biotic (i.e. species‐to‐species associations) predictors. Our results indicate that in addition to the direct loss of resource‐specialised species, forest management has indirect effects mediated through interactive associations. In particular, species with strong associative links to other species are especially sensitive to forest management.